KANDUNGAN LEMAK KULIT PADA BERBAGAI JENIS AYAM KONSUMSI - Reni Rakhmawati; Mei Sulistyoningsih (Florea : Jurnal Biologi dan Pembelajarannya, 2019)
The fat content has been known to vary so that the physical quality of meat is largely determined by its fat content. The purpose of this study was to determine the skin fat content of various types of chicken consumption. The study was conducted for 1 day at the AsriPlamongan Indah Semarang Housing, and UNDIP's animal husbandry laboratory to examine the skin fat content. The research subjects consisted of 12 chickens consisting of 3 broilers, 3 laying hens, 3 native chickens, 3 male chickens. The research variable is skin fat. The data obtained were analyzed using 5% ANOVA. The results of the study had a significant effect (P> 0.05) of 4 types of chicken on skin fat. Conclusion The fat content of chicken skin in various types of chicken consumption has different levels